Bimbingan Teknik (Bimtek) Penyusunan Program Pembangunan Desa dalam Pemanfaatan Dana Alokasi Desa (ADD) Pada Aparat Desa di Desa Annduna Kecamatan Laeya Kabupaten Konawe Selatan - Suhri Kasim, Syaifudin; Upe, Ambo; Juhaepa; A. Tawulo, Megawati; Basri, Muhammad; Asriani (Indonesian Journal of Community Services, 2022)
There are still several problems in the implementation of Village Fund Allocation (ADD) assistance in Anduna Village, Laeya District. In reality, not all of the sources of revenue from ADD and Village Original Income make a real contribution to village finances. Problems in the implementation of village fund allocations are found in the ability of village heads, elements of village government, and community institutions in the village in preparing village development programs related to the use of funds sourced from the Village Fund Allocation (ADD) so that many programs are carried out not under the needs of the community. Causing the results of the program to be not utilized by the community according to its designation. Through the community service team counseling program from the Faculty of Social and Political Sciences, implementing technical guidance to village heads and their officers as a solution to solving village government problems in managing Village Fund Allocations (ADD).